2019
DOI: 10.1002/clc.23160
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular events and death after myocardial infarction or ischemic stroke in an older Medicare population

Abstract: Background Survivors of myocardial infarction (MI) or ischemic stroke (IS) are at high risk for subsequent cardiovascular events. Hypothesis Older patients with prior MI or IS are at risk for recurrent cardiovascular events, and comorbidities such as diabetes may increase this risk. Methods Two cohorts were studied in a retrospective Medicare 20% random sample—a 2008 cohort with up to 6 years of follow‐up (MI, N = 26 460; IS, N = 17 566) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 32 publications
1
24
0
3
Order By: Relevance
“…In a recently published study of recurrent MI and IS in Medicare beneficiaries, the rate of recurrent IS during the patients' first year of survival after an event of IS (6.7%) was similar to that of patients with recurrent MI (7.2%), which further supports the need for aggressive intervention for secondary prevention in patients with MI or IS. 27 Other important areas for future research will include investigating how the CV risk profile of patients in our cohort compares with the risk profiles defined in the 2018 ACC/AHA guideline, as well as assessing the impact of new guideline and the potential influence on physician prescribing practices for PCSK9 inhibitor therapy in future cohort analyses. Studies that assess the characteristics of filled vs abandoned prescriptions and impact on CV outcomes would also be of interest in the context of the changing value and access landscape for PCSK9 inhibitors.…”
Section: Dovepressmentioning
confidence: 99%
“…In a recently published study of recurrent MI and IS in Medicare beneficiaries, the rate of recurrent IS during the patients' first year of survival after an event of IS (6.7%) was similar to that of patients with recurrent MI (7.2%), which further supports the need for aggressive intervention for secondary prevention in patients with MI or IS. 27 Other important areas for future research will include investigating how the CV risk profile of patients in our cohort compares with the risk profiles defined in the 2018 ACC/AHA guideline, as well as assessing the impact of new guideline and the potential influence on physician prescribing practices for PCSK9 inhibitor therapy in future cohort analyses. Studies that assess the characteristics of filled vs abandoned prescriptions and impact on CV outcomes would also be of interest in the context of the changing value and access landscape for PCSK9 inhibitors.…”
Section: Dovepressmentioning
confidence: 99%
“…Along these lines, Han Jing et al analyzed stroke recurrence in a rural population and found rates similar to those of the ARTPER study: the recurrent stroke rate was 22.5% at five years [ 11 ]. As in other studies, diabetes was an independent risk factor [ 11 , 24 ]. The ARTPER study looked at urban patients who had easy access to the hospital and primary health center.…”
Section: Discussionmentioning
confidence: 91%
“…In our study, the risk of cardiac recurrence (33%) was greater than stroke recurrence (17%). In contrast, the Suying Li et al study [ 11 ] with older patients with a prior MI or stroke, found a smaller difference between recurrence types: the cumulative incidence of recurrence at six years was 14.3% for recurrent MI and 13.4% for recurrent stroke. This difference may be due to the fact that the population in this study was older, was more predominantly female, that follow-up was at six years, or that there was some comorbidity, such as carotid stenosis and endarterectomy.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…При этом по сравнению с первым месяцем с 31-го дня до 1 года происходил резкий спад заболеваемости инсультом (в 3,1 раза) [6]. Частота развития инсульта через 1 мес после развития ИМ составляет 1,2% [20], в течение года после ИМ инсульт развивается у 1,7-2,1% больных [21,25]. Согласно анализу крупных исследований в течение первого года после ИМ частота развития ишемического инсульта составляет 4,1% [11,23].…”
Section: Myocardial Infarction Complicated By Ischemic Stroke инфарктunclassified